2011
DOI: 10.1103/physrevlett.107.225901
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Irreversibly Adsorbed Layer on Local Viscosity of Nanoconfined Polymer Melts

Abstract: We report the origin of the effect of nanoscale confinement on the local viscosity of entangled polystyrene (PS) films at temperatures far above the glass transition temperature. By using marker x-ray photon correlation spectroscopy with gold nanoparticles embedded in the PS films prepared on solid substrates, we have determined the local viscosity as a function of the distance from the polymer-substrate interface. The results show the impact of a very thin adsorbed layer (~7 nm in thickness) even without spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
223
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(237 citation statements)
references
References 38 publications
(68 reference statements)
12
223
2
Order By: Relevance
“…Also, the values of δ are not too different from those extracted for polymers on a flat substrate. 15,16 Although, the actual effective viscosity experienced by the PGNPs in the film could have various factors (including intrinsic viscosity gradients in PS films 30 ), based on the above discussion, we postulate that it is largely due to the existence of an interface viscosity, η s (especially for 39 nm films), which is different from the bulk viscosity, η, as indicated in the schematic in Fig. 3(d).…”
Section: (A)-2(b))mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the values of δ are not too different from those extracted for polymers on a flat substrate. 15,16 Although, the actual effective viscosity experienced by the PGNPs in the film could have various factors (including intrinsic viscosity gradients in PS films 30 ), based on the above discussion, we postulate that it is largely due to the existence of an interface viscosity, η s (especially for 39 nm films), which is different from the bulk viscosity, η, as indicated in the schematic in Fig. 3(d).…”
Section: (A)-2(b))mentioning
confidence: 99%
“…We now use the well known temperature dependence of bulk viscosity of PS 38 to obtain the expected viscosity of the PNC films at each temperature for all the films. Although, existence of confinement effects on viscosity of thin polymer films has been widely discussed with a great deal of controversy 30,33 we have avoided usage of any such data or models. In any case we assume that any possible viscosity anomalies which exist in our films occur mostly at lower temperatures (near their T g ) and at the highest measured temperature at which our dynamics data exists, these anomalies would be minimal and it is, therefore, safe to assume bulk-like viscosity at the highest measured temperature.…”
Section: (A)-2(b))mentioning
confidence: 99%
“…Recently, Koga et al [20,29] explained the observed interfacial slowing down in supported thin films in terms of a bound loop layer (BLL) made of the loops of the adsorbed chains. According to them [20,29], the average height of the BLL provides a good estimate for the thickness of the DIL that experiences slower dynamics.…”
mentioning
confidence: 99%
“…According to them [20,29], the average height of the BLL provides a good estimate for the thickness of the DIL that experiences slower dynamics. Considering the analogy between polymer thin films and PNCs [7,30], it is reasonable to anticipate a similar interfacial chain packing-dynamics relationship in PNCs [31,32].…”
mentioning
confidence: 99%
“…Understanding and prediction of equilibrium and dynamic properties of fluids and their mixtures in nanopores are of considerable importance in various industrial processes and scientific fields such as separation of mixtures by porous materials, wetting, lubrication, and tribology. [1][2][3] A lot of methods have been used to represent the inhomogeneous behavior of confined fluids from experimental measurements, molecule simulations to theoretical models, and the classical density functional theory (DFT) in general provides reasonable description of inhomogeneous fluids with moderate computational cost. 4 A variety of DFT models have been developed to predict the properties of inhomogeneous simple atomic and complex fluids, and those based on Wertheim's first order thermodynamic perturbation theory (TPT1) are promising.…”
Section: Introductionmentioning
confidence: 99%